Pertumbuhan Ekonomi Negara ASEAN : Peran Teknologi Informasi, Pendidikan dan Investasi Asing - Irva Nadya; Hasdi Aimon (Universitas Negeri Padang, 2020)
This research study recognizes the role of (1) Information and Communication Technology on Economic Growth in ASEAN countries, (2) Education level on Economic Growth in ASEAN countries, (3) Direct Foreign Invesment on Economic Growth in ASEAN countries using the method multiole linear equations with Least Panel Square Model data from 2013 to 2018. Estimation results from multiple linear equations show that (1) ICT hs a significant positive effect on economics in ASEAN countries (2) Education level has significant positive effect on growth in ASEAN countries and (3) Foreign Direct Invesment has a significant positive effect on Economic Growth i ASEAN countries.